The Whitening, Moisturizing, Anti-aging Activities, and Skincare Evaluation of Selenium-Enriched Mung Bean Fermentation Broth - Wei, Kang; Guo, Congyin; Zhu, Jiangxiong; Wei, Yang; Wu, Meirong; Huang, Xiaodong; Zhang, Mu; Li, Jide; Wang, Xueyun; Wang, Yuanfeng; Wei, Xinlin (Frontiers in Nutrition, 2022)
Selenium-enriched mung bean (Se-MB) is a combination of mung bean (MB) and selenium (Se), which have a variety of potential biological activities. However, little is known about the skincare activity of Se-MB. The chemical composition of Se-MB fermentation broth (Se-MBFB) was analyzed to investigate the whitening, moisturizing, and anti-aging activities of Se-MBFB. The tyrosinase inhibition, anti-melanogenic in melanocytes (B16F10 cells), and moisturizing effect in human dermal fibroblasts (HDFs) were analyzed. Besides, the free radical scavenging activity of Se-MBFB was assessed in vitro. To verify the in vivo effects and the potential of practical applications of Se-MBFB, a clinical trial was conducted on the participants: 31 Chinese women aged 25–60 years, with no pigmentation disorder, no illness, no history of hypersensitivity reaction, and no use of skincare product on the face. The participants used an Se-MBFB masque for 15-20 min after cleaning the face. The measurement points were Week 0, 2, and 4 (W0, W2, and W4) after using the masque, and target sites were cheek and canthus. The following parameters were recorded on the target sites at each visit: melanin index, skin color, cuticle moisture content, transepidermal water loss, and crow's feet. The results demonstrated that Se-MBFB was rich in polyphenols, peptides, and γ-aminobutyric acid (GABA), displayed significant free radical scavenging and tyrosinase inhibiting activities, decreased the synthesis of melanin, and upregulated the aquaporin-3 (AQP3) expression. The test of the Se-MBFB mask showed that after 4 weeks of using the Se-MBFB facemask, the faces of the participants became whiter with reduced wrinkles and increased moisture content. Se-MB possessed the excellent whitening, moisturizing, and antioxidant efficacy, which could lay a scientific foundation for utilization and development of skincare products of Se-MB and its related industrial cosmetics products.